Analisis Perbandingan Kebutuhan Modal Kerja dengan Metode Working Capital Turnover dan Net Trade Cycle (Studi Kasus: Pabrik Tahu UD Sumber Makmur) - Yuniarti, Emma Lulun; Adiyanto, Mochamad Reza (JURNAL ADMINISTRASI KANTOR; Vol 12 No 1 (2024): Jurnal Administrasi Kantor (Juni 2024)DO - 10.51211/jak.v12i1.2974, 2024)
This research aims to find out how much working capital is needed and compare the results of calculating working capital requirements based on the method working capital turnover and net trade cycle at the UD Sumber Makmur tofu factory for six years. The type of research used is a quantitative method with a descriptive approach by collecting data obtained from the UD Sumber Makmur tofu factory industry through interviews. The author has processed the data into financial reports in the form of balance sheets and profit and loss reports so that it can provide a clear enough picture for the author to analyze and compare with existing theories. The data source in this research is primary data obtained through interviews and direct observation. In analyzing the comparison of working capital, calculations are carried out using the method working capital turnover and net trade cycle. Results of calculations of projected working capital requirements with working capital turnover in 2024 it will be Rp 725,723,018 then in 2025 it will increase by Rp 1,045,079,949. Meanwhile, the projection of working capital needs uses the method net trade cycle in 2024 it will be Rp 116,479,521, then in 2025 it will increase by Rp 121,485,100. So the comparison of this research shows that the need for working capital is based on the method working capital turnover gives greater results compared to using the method net trade cycle.   Keywords: Working Capital Requirements, Working Capital Turnover, and Net Trade Cycle